Grafting to denuded nasal cavity for prevention of recurrent nasal polyposis by endoscopic sinus surgery - Amin, Hany; Mandour, Yasser Mohammed Hassan; Elrefai, Ahmed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The objective of the study was to avoid nasal polyposis occurrence after recurrent FEES. Methods: 87 patients undergoing recurrent FESS due to recurrent nasal polyposis, after completing all steps of FESS the placement of normal nasal mucosa from inferior turbinate or nasal septum instead of the mucosa of the fovea ethmoidalis and lamina papyracea was done. Results: There were nasal obstruction improvement in 79 patients (90.8%), but there were 8 patients (9.2%) had recurrent nasal polypi causing nasal obstruction. There was smell improvement in 38 patients (71.7%) out of 15 patients (28.3%). Conclusions: The nasal cavity grafting in FESS of recurrent nasal polyposis with nasal septal or inferior turbinate mucosa had promising results in prevention of nasal polyposis recurrence. These results made a recommendation of nasal cavity grafting during primary FESS of nasal polyposis.